Implementation of Asymmetrical Decentralization In Papua: Relevance to Demands and Problems - Angela, Deni; Nursadi, Harsanto (Fiat Justisia: Jurnal Ilmu Hukum, 2024)
This research aims to analyze the implementation of asymmetric decentralization in Indonesia with the case study of Papua. Efforts to end the conflict in Papua are a priority for the Indonesian government. This research uses qualitative research methods packaged in a normative legal approach, including historical and legal approaches as primary sources for research. Based on the special autonomy law, there’s potential and equitable development through articles that provide opportunities for Indigenous Law 2/21. Because several changes lead to equality and the elimination of inequality. However, in practice, asymmetric decentralization can possibly become a problem, especially regarding the threat of conflict due to expansion and acts of corruption, collusion, and nepotism. In practice, several indicators have not been able to provide a solution to the separatism movement in Papua, especially regarding the peace agreement. The Implementation of special autonomy has not been a complete solution. Meanwhile, in the relevance of special autonomy, Law 2/21 sporadically has been by the requests represented DPRD included in the expense of discrimination and development allocation. However, in several demands, the Indonesian government has not been able to answer one of which is dialogue and openness of journalistic activities.